Bit-filling algorithm for fast subcarrier-selecting in ultrasonic through-metal communication - Linsen XU; Wei YANG; Hongxian TIAN; Tao WU (Tongxin xuebao)
Aiming at the high complexity of the greedy bit-filling algorithm,a bit-filling algorithm for fast subcarrier-selecting used in ultrasonic through-metal communication was proposed.The approximate expression for the BER increment,which was used as the basis for selecting subcarriers in the greedy bit-filling algorithm,was derived by the BER approximation formula and Taylor formula.The subcarrier was selected first and then its BER was calculated.Therefore,it was unnecessary for the greedy bit-filling algorithm to calculate new BER of all subcarriers.The simulation results show that the proposed algorithm can achieve nearly the same data rate as the greedy bit-filling algorithm and save the BER calculation of about 3 4 subcarriers,greatly reducing the amount of calculation.